Dietary Acid Load and Bone Health: A Systematic Review and Meta-Analysis of Observational Studies - Gholami, Fatemeh; Naghshi, Sina; Samadi, Mahsa; Rasaei, Niloufar; Mirzaei, Khadijeh (Frontiers in Nutrition, 2022)
Findings on the association between dietary acid load (DAL) and bone health are conflicting. This study aimed to summarize available studies on the association between DAL and risk of fractures or bone mineral density (BMD) in adults. Online databases including PubMed, Scopus, and Embase were searched for relevant studies published up to June 2021, using pertinent keywords. We identified observational studies (cohort, case-control, and cross-sectional) investigating the association between DAL and risk of fractures or BMD, then selected studies following these reported criteria: RRs with corresponding 95% CIs for the relationship between DAL and fracture risk; correlation coefficients for the association between DAL and BMD; and mean ± SD of BMD values across the categories of DAL. Overall, 17 studies with 80545 individuals were included. There was no significant relationship between the PRAL and fracture risk (Pooled RR: 1.18; 95% confidence interval 0.98 to 1.41, I2 = 60.6%). Moreover, a similar association was observed between the NEAP and fracture risk (Pooled RR: 1.41, 95% CI: 0.79 to 2.52, I2 = 54.1%). The results of five studies from four publications revealed no significant association between dietary PRAL score and femoral and spinal BMD (WMD femoral = -0.01, 95% confidence interval: -0.02 to 0.01, I2 = 76.5%; WMD spinal = -0.01, 95% CI: -0.03 to 0.01, I2 = 56.7%). However, being in the highest category of NEAP was significantly associated with a lower femoral and spinal BMD (WMD femoral = -0.01, 95% CI: -0.02 to -0.00, I2 = 82.1%; WMD spinal = -0.02, 95% CI: -0.03 to -0.01, I2 = 93%). It was showed that adopting diets high in acidity was not associated with risk of fractures. We also found a significant negative relationship between NEAP and BMD. However, DAL based on PRAL was not associated with BMD.